Optimal Continuous Cover Forest Management with a Lower Bound Constraint on Dead Wood. Issue 2 (10th December 2019) - Rämö, Janne; Assmuth, Aino; Tahvonen, Olli
Abstract: We analyze economically optimal continuous cover forestry with dead wood as a biodiversity indicator. We study mixed-species stands consisting of Norway spruce ( Picea abies [L.] Karst.), birch ( Betula pendula Roth.), and other broadleaves (e.g., oak [ Quercus sp.], maple [ Acer sp. ]). The analysis is based on an economic description of continuous cover forest management using an empirically estimated size-structured transition matrix model. We use size-specific decomposition rates for dead wood, with the lower limit on total dead wood volume varying between 0 and 40 m 3 ha –1 . The optimization problem is solved in its general dynamic form using gradient-based interior point methods. Increasing the dead wood volume requirement affects total stand density only slightly, but increases stand heterogeneity as other broadleaves are grown in higher numbers. In addition, increasing the dead wood requirement has only a minor effect on the total felled volume, but harvests shift from timber harvests to biodiversity fellings to maintain the required dead wood volume. In the optimal steady state with a high dead wood requirement, two harvesting cohorts emerge: one for timber harvests and the other for biodiversity fellings. Increasing the dead wood requirement decreases steady-state net timber income by up to 30 percent compared to the unconstrained solution.